Simultaneous supplementation of the microbial fraction of kefir containing Lactiplantibacillus plantarum subspecies plantarum strains and antibiotic growth promoters on performance, gut microbiota, and health parameters in broiler chickens - Franco, Mariana C.; Soria, Mario; Federico, Francisco Javier; Zapata, Roberto A.; Hamet, María Fernanda; Gallinger, Claudia Isabel; De Antoni, Graciela L.; Peláez, Angela M.L.; Basiouni, Shereen; Bueno, Dante Javier (German Multidisciplinary Publishing Center (GMPC), 2025)
Kefir contains lactic acid bacteria and yeasts, which are involved in fermentation and contribute to its probiotic effects. The simultaneous supplementation feeding of antibiotics and probiotics could serve as a way to replace antibiotic growth promoters (AGP) gradually. So, this study was conducted to evaluate the effect of the microbial fraction of kefir and four strains of Lactiplantibacillus plantarum subsp. plantarum (MFKLP) with promising in vitro probiotic properties, applied in drinking water, and AGP on different parameters in broiler chickens for 28 days. Compared to AGP alone, the MFKLP-AGP consumption decreased the percentage of liver lipids by 24% and 34% at 21 and 28 days of age, respectively. Furthermore, it modified the percentage of some types of leukocytes. It decreased the percentage of eosinophil from 1.8% to 0.2% at day 7, decreased the percentage of lymphocytes, and increased the percentage of heterophils and the heterophil/lymphocyte ratio from 72.8% to 58.6%, 21.6% to 34.8%, and 0.3 to 0.6 at 21 days of age, respectively, and increased the percentage of monocytes from 4.7% to 5.4% at 28 days of age. It also increased the percentage of monocytes at 28 days of age and decreased the crypt depth, and increased the villus height to crypt depth ratio and microbial community diversity at days 21 and 28. The concurrent supplementation of MFKLP and AGP is beneficial for gut and liver health, and this supports the case for continuing research into the use of MFKLP for developing health-promoting functional feed for poultry.